Thoracic damage control surgery - Gonçalves,Roberto (2016)
ABSTRACT The damage control surgery came up with the philosophy of applying essential maneuvers to control bleeding and abdominal contamination in trauma patients who are within the limits of their physiological reserves. This concept was extended to thoracic injuries, where relatively simple maneuvers can shorten operative time of in extremis patients. This article aims to revise the various damage control techniques in thoracic organs that must be known to the surgeon engaged in emergency care.